A New Possibility of Introducing Third Persons’ Assessment in a Class – An Experiment to Stimulate Active and Autonomous Learning in the Class: Exploring the Impact of Third Persons' Assessment on Learners' Motivation and Autonomy in Language Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Active Learning has started to be given a greater importance since the late 1970s in the educational field. Moreover, in foreign languages education, Learning Autonomy has been studied from 1990s. Those movements occurred to break away from the traditional methods of teaching and to develop a new educational methodology which encourage learners to learn actively and autonomously so that they can find the way to solve problems by themselves in the society which has started to change rapidly these days as technology evolves.In the process of Active Learning or Autonomous Learning, the way of assessment also should be reconsidered. In the traditional education, the teacher is the only person who assesses the students’ activity. However, when Active Learning or especially Autonomous Learning is introduced in a class, the evaluator can be the students themselves or even a third person as in a person outside of the class as well.To see the effect of third persons’ assessment on the learners’ motivation, two Japanese language classes held in EFL-University in 2017 and 2018 were compared, in which the teachers gave students a project work to make videos. In one class the project work was assessed only by the teacher, in the other class they uploaded the videos on YouTube and had the opportunity to observe the reactions from outside the class. Having a questionnaire about those two classes to the students, the effect of the assessment from third persons were observed and the possibility of introducing third persons’ assessment as an effective tool to increase learners’ motivation and autonomy to study was explored.